How Institusional and Manajerial Ownership, Transfer Pricing and Company Size Affect Tax Avoidance? - Rizki , Mochamad; Nugroho, Lucky (LifeSciFi, 2024)
This research explores the influence of institutional ownership, managerial ownership, transfer pricing, and company size on tax avoidance in consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The study adopts a quantitative research approach, using secondary data derived from financial and annual reports available on the IDX. Employing a purposive sampling technique, the study selected 31 companies, resulting in 155 data samples for analysis. Stata 18 was used as the primary analytical tool. The findings indicate that institutional ownership and transfer pricing significantly affect tax avoidance, suggesting that the presence of institutional investors and corporate strategies involving transfer pricing are critical in influencing tax-related behaviors. Conversely, managerial ownership and company size do not exhibit a significant impact on tax avoidance. These results underscore the role of institutional control and strategic financial practices in shaping tax planning activities. This study contributes to the broader discourse on corporate governance and tax planning in Indonesia, offering valuable insights for policymakers and stakeholders aiming to mitigate tax avoidance and enhance compliance in the consumer goods sector.